Has trade liberalization in South Africa affected men and women differently? - Thurlow, James (International Food Policy Research Institute, 2006)
Trade liberalization is a central part of South Africa’s post-Apartheid development strategy. However, despite considerable reforms, the country has failed to generate pro-poor growth, with both unemployment and inequality worsening over the last ten years. This has raised concern that trade liberalization may have worked against the country’s development objectives. This study uses a dynamic general equilibrium and microsimulation model to assess the effects of trade liberalization on growth, employment and poverty in South Africa. More specifically, it examines how men and women have been affected differently and whether liberalization has contributed to the faster rise in female unemployment and poverty. The results suggest that trade policies have not contributed to increased poverty and that trade-induced technological change has accelerated growth. However, liberalization has changed the sectoral structure of production and has exacerbated income inequality. While male and female workers have benefited from trade-induced growth, it is male-headed households who have benefited more from rising factor incomes. Trade reforms have however contributed to the observed decline in the gender wage gap, but this has been driven by rising employment amongst higher-skilled female workers. As such, the decline in poverty amongst female-headed households has remained small. While further liberalization may increase growth and reduce poverty, it is men and male-headed households who are more likely to benefit. These findings suggest that, while there is no trade-off between trade reform and poverty reduction, the country should not rely on further liberalization to generate pro-poor growth or address the prevailing inequalities between different population groups, such as men and women.